2014
DOI: 10.1007/s13224-014-0532-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Position of the Copper T 380A as Determined by the Ultrasonography Following its Insertion in the Immediate Postpartum Period with the Subsequent Complications: An Observational Study

Abstract: Purpose Incorrectly placed copper T 380A leads to increased contraception failure. This study aimed to find an association between the ultrasonographic position of the copper T 380A in the immediate postpartum period and the adverse effects observed during the period of 6 months after its insertion. Methods This descriptive study was carried out in the Department of Obstetrics & Gynaecology of a tertiary-carecenter of India from September 2011 to February 2013. The women eligible for immediate postpartum coppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…7,18,19 Twenty-two studies included only CuT380A IUDs, 8,16–18,20–37 13 included only LNG-IUS, 19,3849 and nine included a mix of the two 7,9,10,14,5054 ; the remaining four studies included CuT200 55–57 or Cu7 IUDs. 58 Twenty-eight studied women with IUDs placed only in the immediate postpartum period, 9,10,14,17,18,21,23,24,26–30,3237,4043,5254,57,58 four studied only early postpartum placements, 44,47,55,56 and the remaining 16 studied more than one placement period. 7,8,16,19,20,22,25,31,38,39,45,46,48–50,51 Similar numbers of studies evaluated vaginal and cesarean deliveries, with 14 including only vaginal deliveries, 14,16,19,20,22,31,34,39,42,44,45,48,53,5816 including only cesarean deliveries, 7,8,17,18,27–30,35,37,38,40,41,43,46,54 16 including both delivery methods, 9,10,21,…”
Section: Resultsmentioning
confidence: 99%
“…7,18,19 Twenty-two studies included only CuT380A IUDs, 8,16–18,20–37 13 included only LNG-IUS, 19,3849 and nine included a mix of the two 7,9,10,14,5054 ; the remaining four studies included CuT200 55–57 or Cu7 IUDs. 58 Twenty-eight studied women with IUDs placed only in the immediate postpartum period, 9,10,14,17,18,21,23,24,26–30,3237,4043,5254,57,58 four studied only early postpartum placements, 44,47,55,56 and the remaining 16 studied more than one placement period. 7,8,16,19,20,22,25,31,38,39,45,46,48–50,51 Similar numbers of studies evaluated vaginal and cesarean deliveries, with 14 including only vaginal deliveries, 14,16,19,20,22,31,34,39,42,44,45,48,53,5816 including only cesarean deliveries, 7,8,17,18,27–30,35,37,38,40,41,43,46,54 16 including both delivery methods, 9,10,21,…”
Section: Resultsmentioning
confidence: 99%
“…One observational study of 100 women who underwent CuT380A insertion after vaginal delivery or cesarean section found that 44% had malpositioned IUDs. Women with malpositioned IUDs were more likely to have had the IUD placed after vaginal delivery than after cesarean delivery and were more likely to report complications by 6 months postpartum, including expulsion, irregular bleeding, and lower abdominal pain [65]. It is uncertain whether asymptomatic partial expulsions or malpositioned IUDs, found after IUD placement in any time frame, are clinically significant.…”
Section: Use Of Ultrasound For Follow-up and Surveillancementioning
confidence: 99%
“…This study finding are comparable to the previous studies done by Gupta et al in 2014 having normally placed PPIUCD in 56% and malposition in 44% cases. 12 In total 200 subjects, PPIUCD insertion was done by consultants in 14 cases (7%), by DNB residents in 74 cases (37%) and by senior residents in 112 cases (56%).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are comparable to previous study done by Swati et al which shows malposition in vaginal delivery group (68.2%) and in LSCS group (31.8%). 12 Data on comparison of effect of expertise on malpositioning shows that among all the 4 malpositions the order was consultants<senior resident<DNB resident but in lateral type of malposition this order is changed making p value significant because total number of PPIUCD insertion done by consultants were less and all the malpositon was of lateral type. Previous studies reveal that among all the malpositon, lateral position was best having minimal or less complications and effective as like normally placed PPIUCD.…”
Section: Discussionmentioning
confidence: 99%